2020
DOI: 10.3233/jad-191246
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Predictors of Cerebrospinal Fluid Cholesterol Efflux Capacity from Neural Cells, a Family of Biomarkers for Cholesterol Epidemiology in Alzheimer’s Disease

Abstract: Background: Basic research has implicated intracellular cholesterol in neurons, microglia, and astrocytes in the pathogenesis of Alzheimer's disease (AD), but there is presently no assay to access intracellular cholesterol in neural cells in living people in the context of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 58 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…Likewise, cholesterol efflux to the CSF from ApoE3 carriers was significantly increased compared to that from ApoE4 carriers in ABCA1-induced BHK cells [ 110 ]. Despite the importance of these findings, only one work has performed similar studies in cells that are functionally and morphologically relevant in the brain and, thus, for AD pathology [ 151 ], representing a proof of concept for CSF cholesterol efflux quantification in human neurological cells. Efflux measurement in neurons, microglia, and astrocytes allowed researchers to conclude that CSF cholesterol efflux levels are positively correlated with total cholesterol, ApoA-I, ApoE, and ApoJ concentrations.…”
Section: Hdl-mediated Cholesterol Trafficking In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, cholesterol efflux to the CSF from ApoE3 carriers was significantly increased compared to that from ApoE4 carriers in ABCA1-induced BHK cells [ 110 ]. Despite the importance of these findings, only one work has performed similar studies in cells that are functionally and morphologically relevant in the brain and, thus, for AD pathology [ 151 ], representing a proof of concept for CSF cholesterol efflux quantification in human neurological cells. Efflux measurement in neurons, microglia, and astrocytes allowed researchers to conclude that CSF cholesterol efflux levels are positively correlated with total cholesterol, ApoA-I, ApoE, and ApoJ concentrations.…”
Section: Hdl-mediated Cholesterol Trafficking In the Cnsmentioning
confidence: 99%
“…Efflux measurement in neurons, microglia, and astrocytes allowed researchers to conclude that CSF cholesterol efflux levels are positively correlated with total cholesterol, ApoA-I, ApoE, and ApoJ concentrations. However, demographic and clinical data were unknown because the CSF samples were taken from anonymous patients, making it impossible to compare efflux among healthy controls and patients with AD [ 151 ].…”
Section: Hdl-mediated Cholesterol Trafficking In the Cnsmentioning
confidence: 99%
“…Two isoforms are encoded by the CLU gene: a truncated nuclear form and a conventional omnipresent secretory heterodimeric disulfide-linked glycoprotein 14 . CLU is highly expressed in patients with diabetes 15 , atherosclerosis 16 , and tumorigenesis 17 . The role of CLU in LFH has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…In serum, ApoA1-containing lipoproteins are the main acceptors and are much higher in concentration than ApoE or ApoJ. Because cellular cholesterol is thought to play a role in AD, we adapted the CEC assay to use neuronal cells as source and CSF as acceptor [ 17 ]. Unlike serum, the concentration of ApoA1 is similar to that of ApoE and ApoJ in CSF such that all three may play a major role in efflux.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike serum, the concentration of ApoA1 is similar to that of ApoE and ApoJ in CSF such that all three may play a major role in efflux. Initial studies have shown that among the cells and conditions used, neuronal cells are a less important source cell than microglia, showing less efflux to ApoA1 and HDL [ 17 ].…”
Section: Introductionmentioning
confidence: 99%